Development of new terminal node controller to improve packet radio transmission for field data acquisition / Mohamad Syahmi Zullkiffle - Zullkiffle, Mohamad Syahmi (2015)
The existing terminal node controller (TNC) has problem during transmit and receive packet of data as a result of noise interference during the transmission of packet data. Implementation of packet radio network in field data acquisition should have a good performance of TNC. This project will improve the performance of existing TNC in packet radio transmission for field data acquisition. The modem integrated circuit, MX614 (Bell 202 Compatible Modem) is applied in the circuit to minimize the noise interference and improve the performance of TNC in data transmission. The modem integrated circuit of MX614 has the capability to filter and equalize the input signal as well as filter and buffer the output signal. This modem integrated circuit converts the data received from microcontroller into 1200 bps audio tones. The features of this modem integrated circuit will improve the performance of TNC in packet data transmission